Analisis Kebutuhan Pembelajaran Holistik Integratif pada Lembaga PAUD - Siti Fardianti Suli; Meutya Amalia Pikoli; Nur Apni; Rosnawati Poloding; Riska Panto; Siti Fadila; Annisa Fahmi Mannassai (INDO PUBLISHING, 2026)
This study aims to analyze the needs of holistic-integrative learning in Early Childhood Education (ECE) institutions. The research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving principals, teachers, and parents as research informants. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that the implementation of holistic-integrative learning plays a significant role in supporting optimal early childhood development through the integration of educational, health, nutritional, parenting, protection, and welfare services. The main needs identified include improving teacher competencies, strengthening collaboration between schools and parents, providing adequate facilities and infrastructure, and enhancing cross-sector partnerships. Supporting factors include teacher commitment, school leadership support, parental involvement, and a conducive learning environment. Meanwhile, inhibiting factors consist of limited human resources, insufficient training opportunities, inadequate facilities, and suboptimal interagency coordination.The study concludes that needs analysis is a strategic step in improving the quality of holistic-integrative services in early childhood education institutions. Addressing the identified needs can assist ECE institutions in developing more effective, integrated, and child-centered services that support optimal child development.